Motives for the sixth preparatory students to rely on YouTube learning videos: (a study according to the theory of dependency on the media) - Hassan Mahmood, Yousif (Al-Adab Journal, 2021)
This research came under the title (Motives for the sixth preparatory students to rely on YouTube learning videos - a study according to the theory of dependency on the media-), and it defines the main objective as it is clear from the title of the research in Knowing the motives for the sixth preparatory students' accreditation on YouTube videos, and according to this main goal, a number of sub-goals have been formulated, which are as follows:Disclosure of materials in which students rely more on YouTube videosInvestigate the length of time students spend watching these videosKnowing the kind of educational material students are trying to obtain in YouTube videosKnowing the reasons for students' reliance on these educational filmsOur research community was the sixth preparatory students, and its sample consisted of 200 of the sixth preparatory students (male and female) and its scientific and literary branches in the district of Tarmiyah.This research is considered descriptive research that is used to study the public by relying on the survey method. As for the tool, it was a questionnaire form, and the most important results that emerged to us are:The highest reliance on educational videos in YouTube was in mathematics with 89%, followed by physics with 84%, then chemistry with 81%.It was found that the weekly time period for watching the videos (from one hour - less than 3 hours) was the highest for most subjects, followed by (from 3 hours - less than 6 hours. (The results showed that most of what students are looking for in educational videos is (solutions to problems), followed by a search for (explanation of materials).Regarding the reasons for relying on videos, the most of them were (an attempt to increase understanding after the teacher’s explanation of the subject) then (obtaining additional information), and then (compensating me for private lessons).